Nominee Agreement dalam Pengalihan Kepemilikan Saham Perseroan Terbatas Ditinjau dari Aspek Hukum Perjanjian dan Hukum Perseroan Terbatas - Fitri Riani Baharudin; Lastuti Abubakar; Tri Handayani (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Nominee agreement as development of agreement is an implementation of the unnamed agreement (innominaat) regulated in Article 1319 of the Civil Code. The existence of this agreement in Indonesia does not constitute a form of agreement that violates the provisions of contract law even though it has not been regulated expressly and specifically. However, if the agreement is made in conflict with or not in accordance with the provisions of the laws in force in Indonesia, then this would cause legal problems. This research method was carried out using a normative juridical approach with descriptive analytical research specifications. The results of this research show that the position of the nominee agreement in the transfer of share ownership is null and void. By making the agreement null and void, it returns the parties to their original state and has implications for the company.